Can Digital Tools Help Sustain Customer Loyalty Amid the Economic Crisis? Evidence from the Telecom Sector - Hammami, Samir; Samman, Hazem Ghaleb Al; Durrah, Omar; Banu, Mahjabin; Alhousary, Tareq (Indonesian Journal of Sustainability Accounting and Management, 2024)
This research examines how to enhance customer loyalty in the telecom sector in terms of economic challenges. A conceptual model was developed and tested empirically by employing structural equation modelling techniques using data collected through a questionnaire from 250 samples working in the telecom sector in Syria. The results showed that customer relationship management (CRM) system, organisational management, and staff readiness significantly and positively affect customer loyalty. The study shows how digital tools influence customer retention in a challenging context, contributing to knowledge of crisis management and consumer behaviour in unstable markets. Practically, the study offers telecom companies strategies for improving customer relationships and maintaining market share using digital solutions during economic difficulties. The research explores the potential of digital technology to enhance social stability and economic resilience by retaining customers and fostering connectivity and access to essential services in challenging economies. This study is one of the first to investigate the relationship between its constructs in its setting.